The Role of Subject Teacher Deliberation (MGMP) in Improving The Competence of Social Science Education Teachers in Junior High Schools (SMP). - Ambarita, Ratoga; Sihole, Beresman; Panjaitan, Friska; Napitu, Ulung; Sinurat, Anggiat (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Subject Teacher Deliberation (MGMP) is a forum for meeting subject teachers in schools. This organization was formed as a forum for meeting subject teachers, but also as a means of friendship and as an organization that accommodates various teacher ideas and also as an accommodating means to various problems faced by teachers in their respective schools. This proves that the importance of the formation of MGMP in overcoming the problems faced by teachers in their respective education units. Through MGMP, it is hoped that teachers can maintain the quality of their performance in carrying out their duties as teachers in accordance with the needs of the community, especially in the world of work. Mgmp's participation in the process of improving teacher performance is necessary to make various breakthroughs that will build a quality education.The purpose of this study is to determine the role of MGMP in improving teacher competence. The results will be a guide in the teaching process so as to produce teachers who have good performance